Terrestrial isopods of the genus Schizidium Verhoeff, 1901 (Isopoda; Armadillidiidae) from the Hyrcaian Forest in northern Iran, including the description of a new species - Abedini, Ahdiyeh; Sari, Alireza; Mohammadi-Kashani, Ghasem (Zootaxa, 2025)
In the present study, the genus Schizidium was investigated in northern Iran. New distributional data for S. persicum is presented and a new Schizidium species is described, with its diagnostic characters illustrated. The new species can be distinguished by its unique coloration and schisma, with the inner lobe slightly shorter than the outer one.